Ceramic materials based on lanthanum zirconate for the bone augmentation purposes: cytocompatibility in a cell culture model - Maria Ulitko; Yulia Antonets; Irina Antropova; Albert Mullabaev; Elena Volokitina; Anna Kasyanova; Ekaterina Loginova; Nataliia Tarasova (Chimica Techno Acta, 2023)
Creation of new ceramic materials for the bone augmentation purposes that combine the absence of cytotoxicity, high strength and osseointegration characteristics is an urgent modern task. In this work, the cytocompatibility of ceramic materials based on lanthanum zirconate (La2Zr2O7) was determined to assess the prospects for their use as implants and components of human joint endoprostheses. The effect of ceramic materials based on undoped and alkali-earth (Ca, Sr) doped La2Zr2O7 on the viability and proliferative activity of human cells was evaluated. The release of elements into the culture medium was also evaluated.